HUMAN RESOURCE DEVELOPMENT ROADMAP IN ISLAMIC EDUCATIONAL INSTITUTIONS: A COMPREHENSIVE REVIEW OF THE HUMAN CAPITAL MODEL BASED ON PROPHETIC VALUES - Muhammad Bahy Naufal; Moh. Anwar; Imron Fauzi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
The development of human resources (HR) in Islamic educational institutions is an important issue in the midst of the challenges of globalization and rapid social change. This research aims to identify and formulate a strategic roadmap in human resource development that integrates prophetic values into contextual human capital models. The research method used is literature study and qualitative analysis of various relevant sources, including the latest scientific journals and articles. The results of the study show that the integration of prophetic values, such as honesty and trustworthiness, in the Islamic education curriculum can improve the character and spirituality of students. In addition, the proposed roadmap provides a comprehensive framework for human resource development that focuses not only on academic aspects, but also on character building. The impact of this research is expected to provide guidance for Islamic educational institutions in creating a generation that is intellectually superior and has noble character, so that they are able to contribute positively to society.